Simultaneous Determination of Metformin and Teneligliptin by Liquid Chromatography in tablets - Chaitanya, Sunkara Mrunal (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Metformin and Teneligliptin are used for the treatment of diabetes. A new liquid chromatographic method has been developed for the simultaneous determination of Metformin and Teneligliptin and the method was validated. Materials and Methods: Shimadzu Model CBM-20A/20 Alite, Ultrafast liquid chromatographic system with C8 Phenomenex column (250 mm × 4.6 mm i.d., 5 μm particle size) and PDA detector was used for the simultaneous determination of Metformin and Teneligliptin. A mixture of methanol and formic acid was used as mobile phase with a flow rate of 0.5 ml/min (UV detection at 210 nm). Results and Discussion: Metformin and Teneligliptin have shown linear regression equations, y = 159069.66x - 139280.39 (R² = 0.9998) and y = 4863932.73x - 12592.06 (R² = 0.9999). The LOD and LOQ are found to be 0.7631 μg/mL and 2.3147 μg/mL for Metformin and 0.0029 μg/mL and 0.0084 μg/mL for Teneligliptin respectively. Conclusions: The present liquid chromatographic method is precise, accurate and can be used for the simultaneous estimation of Meformin and Teneligliptin tablets